A SiC-based Rectifier for SCR-based Rectifiers Replacement to Improve the Performance of the Static Exciters in the QAWTP (University of Thi-Qar Journal for Engineering Sciences, 2022)
Due to the thyristors drawbacks, the obsolete driving and control hardware spare parts, and instead of replacing the entire excitation systems, this paper proposes a SiC-based rectifier as a replacement for the SCR-based rectifiers that are used in the exciters to provide the DC field current to the rotors of the synchronous motors in Qarmat-Ali Water Treatment Plant (QAWTP). The system performance is improved and its power density is enhanced by improving the rectifier performance. In addition to the capability to operate in harsh environments and high ambient temperatures, the proposed rectifier minimizes the harmonic contents in the input current and the output voltage. The rectifier is simulated with a maximum current of 200 A which is higher than the current that is measured in the station. The calculated efficiency of the rectifier is about 90%. With a small input passive filter, the archived THD of the input current is 11% with a light load and 22% with a full load.